Parental rejection and internalizing/externalizing problems among left-behind children: the moderating role of interpersonal harmony in class - Liu, Zixiao; Zhao, Zizheng; Chen, Huijing (Frontiers in Psychology, 2024)
Background and objectives Left-behind children are characterized by prolonged separation from one or both parents, which exposes them to a constant lack of good parenting, leading to increased risk of internalizing and (or) externalizing problems. This study explored the effects of parental rejection on internalizing and externalizing problems, and examined the moderating role of interpersonal harmony in class. Methods The sample comprised 3,473 left-behind children (aged 6 15; 54.1% girls) in a rural area of southwest China. Self-reported measures including Parental Acceptance-Rejection Questionnaire, Class Interpersonal Harmony Questionnaire and Child Behavior Scale were administrated. Regression analysis was employed and Hayes PROCESS macro was utilized to test the moderation effect. Results The analysis showed that parental rejection had a significant predictive effect on both internalizing problems (β = 0.33, p < 0.001) and externalizing problems (β = 0.40, p < 0.001) of the left-behind children. Teacher interpersonal climate (β = −0.05, p < 0.001) and peer interpersonal climate (β = −0.04, p < 0.01) significantly moderated the relationship between parental rejection and externalizing problems for children with both parents absence, but not for children with single parent absence. Conclusion Benign teacher interpersonal climate and peer interpersonal climate may buffer the detrimental effect of parental rejection on left-behind children’s externalizing problems.